The indigo jackal and other stories level 3 supplementary reading material - Horsburgh, Nicholas; Oxford university press (Karachi, Pakistan Oxford university press, 2013)
Oxford Reading Treasure is a fun-filled reading package designed for children in the six to ten years' age group. It features 15 books containing tales of laughter, adventure, fantasy, and real life. The books will infuse the joy of reading in young readers and improve fluency and comprehension. Oxford Reading Treasure will aid in developing good reading habits. There are 15 books designed for five graded levels, with three books for each level. Each book contains four to six independent stories Includes vocabulary lists to enhance language development The layout is colourful with attractive illustrations The books are colour-coded for easy identificatio
Keywords: Oxford english textbook